2022
DOI: 10.1002/iub.2661
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐dependent cytolysins: The outstanding questions

Abstract: The cholesterol-dependent cytolysins (CDCs) are a major family of bacterial pore-forming proteins secreted as virulence factors by Gram-positive bacterial species. CDCs are produced as soluble, monomeric proteins that bind specifically to cholesterol-rich membranes, where they oligomerize into ring-shaped pores of more than 30 monomers. Understanding the details of the steps the toxin undergoes in converting from monomer to a membrane-spanning pore is a continuing challenge. In this review we summarize what we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Since VapA is a membrane-active protein, it might well bind more strongly to one membrane curvature over another, but no comparative binding studies have yet been published. Cholesterol, which is required for the binding and function of many bacterial membrane-active proteins ( 38 ), influenced the binding of neither rVapA nor rVapB except that rVapA bound better when PA was also present ( Fig. 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Since VapA is a membrane-active protein, it might well bind more strongly to one membrane curvature over another, but no comparative binding studies have yet been published. Cholesterol, which is required for the binding and function of many bacterial membrane-active proteins ( 38 ), influenced the binding of neither rVapA nor rVapB except that rVapA bound better when PA was also present ( Fig. 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies with toxins such as PLY have shown that CDCs often play important roles in bacterial progression from colonization to infection by contributing to inflammation or transmission [42]. Sublytic concentrations of CDCs can lead to a slew of host cell responses that help bacterial proliferation [44,45]. It is therefore conceivable that TGY could play roles in propagating opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of toxin monomers to the membrane, and their correct insertion and oligomerization into the lipid bilayer, are essential steps common in the action mechanisms of protein toxins acting at the cell membrane. Membrane lipids such as sphingomyelin and cholesterol have been shown for several protein toxins to have an essential role by favoring one or more of these steps [32][33][34]. In recent years, experimental evidences have shown that several RTX toxins including the leukotoxin (LtxA) from Aggregatibacter actinomytemcomitans, the Escherichia coli hemolysin (HlyA) and RtxA cytolysin from Kingella kingae, require membrane cholesterol for their correct lytic functions [35][36][37].…”
Section: Introductionmentioning
confidence: 99%